Addressing the Needs of Diverse Learners in a Christian Online Higher Education Environment - Cole, Brian E. (Christian higher education, 2023)
With the growth of online higher education and the increasing diversification of college and university students, there is a need to focus on addressing the inequities of online learning and responding to the needs of diverse students. Students experience greater challenges in academic performance and in persisting and completing online programs, especially among particular student subgroups and course subject areas. Although research has identified some of the facilitating factors and barriers to online student persistence in coursework, supporting diverse online students requires attention not only to course design and instruction, but also broader institutional commitments. Christian higher education can present unique challenges to these students but might also be able to provide support and remedies that are not immediately available at other types of institutions. This paper synthesizes the literature on the needs of diverse learners in online education and provides an example of how the online campus of Abilene Christian University is attempting to meet the needs of its diverse learners.